Hostility and reactive criminal thinking as mediators of the violent victimization–violent offending relationship: affect before cognition? - Walters, Glenn D. (Criminal justice studies, 2020)
The purpose of this study was two-fold: 1. determine whether an affective-cognitive construct, hostility, and a cognitive-affective criminal thinking style, reactive criminal thinking (RCT), mediate the relationship between prior violent victimization and future violent offending, and 2. ascertain whether mediator order – hostility before RCT and RCT before hostility – makes a difference in the overall results. Using seven waves of data, three overlapping analyses were performed on data provided by 1,354 youth (1,170 males, 184 females; mean age = 16.04 years) from the Pathways to Desistance study. A two-mediator pathway that placed hostility before RCT (Victimization-1/2/3 → Hostility-2/3/4 → RCT-3/4/5 → Offending-4/5/6) proved significant in all three analyses, whereas the alternate two-mediator pathway, in which the order of the two mediators was reversed (i.e. RCT-2/3/4 → Hostility-3/4/5), was non-significant in two out of the three analyses. Five single-mediator pathways, four of which were mediated by hostility, were also significant. Congruent with aspects of both general strain and criminal lifestyle theories, violent victimization appeared to stimulate short-term situational hostility, which, in turn, facilitated or primed formation of reactive criminal thinking and the youth’s eventual participation in criminal violence, although hostility alone had a significant impact on criminal violence as well.